Adolescent females and hormonal contraception: a retrospective study in primary care. - Krishnamoorthy, N; Simpson, C; Townend, J; Helms, P; McLay, J (2008)
PURPOSE: The aim of this study was to assess change in the number of adolescent females prescribed hormonal contraception in primary care following the publication in the United Kingdom of the Social Exclusion Unit report on Teenage Pregnancy. METHODS: We conducted a retrospective observational study of 320 primary care practices in Scotland. Hormonal contraceptive prescribing to girls aged <16 years and those aged 16-19 years was assessed for April 1 to March 31 for the study years 2000-2001 to 2005-2006 from Scottish primary care practice data. RESULTS: Between 2000-2001 and 2005-2006, the proportion of girls aged <16 years and those 16-19 years who were prescribed hormonal contraception by their primary care physicians increased by 82% (p < .001) and 53% (p < .001) respectively. The increase became significant from age 12 years for the combined oral contraceptive, 14 years for the progestogen-only pill, and 15 years for depot progestogens. By 2005-2006, 2.9% of girls aged <16 years and 40.5% of those aged 16-19 years were prescribed some form of hormonal contraception by their primary care physicians. The small number of girls aged <12 years who were prescribed hormonal contraception remained constant over the study period. CONCLUSIONS: Since the publication in the United Kingdom of the Social Exclusion Unit Report on Teenage Pregnancy, there has been a significant increase in the number of female adolescents aged > or =12 years prescribed hormonal contraception by their primary care physicians. However the number of individuals prescribed hormonal contraception still remains relatively low in comparison to the reported levels of sexual activity among adolescents in the United Kingdom.